Remimazolam: An Updated Review of a New Sedative and Anaesthetic - Hu Q; Liu X; Wen C; Li D; Lei X (Dove Medical Press, 2022)
Qinxue Hu1 *, Xing Liu2 *, Chengli Wen,1 Duo Li,3- 5 Xianying Lei1 1Department of Critical Care Medicine, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China; 2Department of Anesthesiology, The Affiliated Hospital of Southwest Medical University, Luzhou, People's Republic of China; 3Department of Respiratory and Critical Care Medicine, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China; 4Department of Inflammation & Allergic Diseases Research Unit, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China; 5Infection Control Department, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Duo Li, Department of Respiratory and Critical Care Medicine, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China, Tel +86 13980241028, Fax +86 830-8950795, Email sclzliduo@163.com Xianying Lei, Department of Critical Care Medicine, The Affiliated Hospital of Southwest Medical University, Luzhou, Sichuan, People's Republic of China, Tel +86 13320741667, Fax +86 830-3165499, Email leixianying310@swmu.edu.cnAbstract: Remimazolam (CNS7056) is a novel benzodiazepine for intravenous sedation; it has an ultra-short duration of action and was recently approved for use in procedural sedation and general anaesthesia. It acts on γ-aminobutyric acid type A receptors and is rapidly converted into an inactive metabolite by tissue esterase enzymes. Remimazolam has been successfully used in endoscopic inspection or surgery and general anaesthesia induction and maintenance with fast and predictable onset and recovery times, high procedure success rates, and minor respiratory and hemodynamic fluctuations and without serious drug-related adverse reactions. If needed, the effects of remimazolam can be reversed by flumazenil, which allows prompt termination of sedation. Although remimazolam has great potential for sedation in patients admitted to intensive care units, future studies are needed to evaluate its efficacy and safety in patients requiring sedation for a long period, and numerous studies are warranted to explore the optimal dose in different application scenarios. The review aimed to provide an introduction to the process of remimazolam synthesis and its current clinical uses and future clinical developments.Keywords: sedation, endoscopy, general anaesthesia, ICU